A Study on clinical patterns of mucocutaneous candidiasis in immunosuppressed patients - Subhashini Mohan (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2017)
Background: Candidasis is the most common superfi cial fungal infection in immunocompromised patients. With the advent of wide spectrum of immunosuppressive drug and increase in HIV patients, there is a change in the epidemiology and clinical presentation of mucocutaneous candidiasis. Aim and Objective: This study has been designed to study epidemiology and the common clinical patterns of mucocutaneous candidiasis in immunosuppressed patients. Materials and methods: A cross sectional study on epidemiology and clinical patterns of mucocutaneous candidiasis among 100 immunosuppressed patients of all age groups attending Dermatology OPD in a tertiary care center. Results: Maximum number of patients were in third and fourth decade. Females were more frequently (73%) affected than males (27%). Type 2 diabetes was the most common cause of immunosuppression followed by steroid intake (20%), cancer patients (10%) and HIV (5%). Oral candidiasis was the frequently observed clinical pattern (48%) followed by vulvovaginal candidiasis (45%), intertriginous lesions on the fingers (2%), toes (2%), and neck (1%). Balanoposthitis was observed in 2% of patients. Limitation: small sample size. Conclusion: Diabetes was the common cause of immunosuppression. Oral candidiasis was the common clinical pattern observed among them.